FAKTOR-FAKTOR YANG MEMPENGARUHI TUMBUH KEMBANG ANAK DI PUSKESMAS DUONO - Krista Fany Dimayu, Jesi; Retnaningsih, Reny; Alim, Zainal (NHM PRESS, 2024)
The aspect of child growth and development is an aspect that explains the process of forming children, both physically and psychosocially. An initial survey conducted on 12 respondents showed that 3 children had questionable growth and development, 1 child had deviant growth and development, and 4 other children had appropriate growth and development. The purpose of this study is to find out the factors that affect the growth and development of children at the Duono Health Center. The research uses an analytical survey method with a Cross sectional approach. The population is all children aged less than 24 months and more than equal to 24-59 months totaling 48 people with a sample taken using the total population technique of 48 people. Data analysis using the Chi-square test. The results of the analysis showed that the p-value = 0.003 for work, education was obtained p-value = 0.000 < 0.05, knowledge was obtained p-value = 0.005 < 0.05, and income was obtained p-value = 0.143 > 0.05. This study concludes that there is an influence of work, education, and knowledge on children's growth and development. Meanwhile, income has no effect on the growth and development of children at the Duono Health Center.